2015
DOI: 10.1002/jctb.4713
|View full text |Cite
|
Sign up to set email alerts
|

A new way of quantifying the production of poly(hydroxyalkanoate)s using FTIR

Abstract: BACKGROUND Conventional techniques used for determination of extractable poly(hydroxyalkanoate)s (PHAs) present in cells are laborious and destructive. Fourier transform infrared (FTIR) spectroscopy is an indirect analytical method to study molecular structures and has been used for the detection and quantification of PHA in intact cells. However, obtain a fine powder with pure PHA to prepare KBr pellets is a difficult task. The objective of this study was to develop a cheap alternative for quantifying the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Especially, the implementation of PAT for polyhydroxyalkanoate (PHA) production can provide significant benefits to facilitate a consistent and highly efficient production. Techniques such as FTIR, Raman spectroscopy, fluorescence staining associated with flow cytometry, and enzymatic approaches were reported as novel methods for a rapid characterization of PHA production [3,4,5,6,7]. A comprehensive overview of qualitative and quantitative methods for PHA analysis was published by Koller et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the implementation of PAT for polyhydroxyalkanoate (PHA) production can provide significant benefits to facilitate a consistent and highly efficient production. Techniques such as FTIR, Raman spectroscopy, fluorescence staining associated with flow cytometry, and enzymatic approaches were reported as novel methods for a rapid characterization of PHA production [3,4,5,6,7]. A comprehensive overview of qualitative and quantitative methods for PHA analysis was published by Koller et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to Porras et al., yeast extract at higher concentrations probably implies an extra supply of nitrogen, which alters the C/N ratio, provoking a less favorable condition for PHA production. [ 30 ] We found that the addition of yeast extract up to the concentration of 0.3% significantly improved bacterial growth and PHB production in B. cereus Y23, 6.82 and 4.03 g L −1 , respectively (Table 5).…”
Section: Resultsmentioning
confidence: 95%
“…The analysis of FT-IR shows the distinguishing peaks from bioplastic. FT-IF has ability to measured functional groups in greater speed and greater sensitivity [21]. FT-IR used it indirect analytical method to study molecular structure 22.…”
Section: Results Of Ftir Spectramentioning
confidence: 99%